2020
DOI: 10.46234/ccdcw2020.165
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Investigation on Residential PM<sub>2.5</sub> Pollution of General Living Scenarios — 12 Cities, China, 2018

Abstract: What is already known about this topic?Residential air pollution can cause a large disease burden, and residential air quality is directly influenced by residential fine particulate matter (PM 2.5 ). Residential PM 2.5 pollution is of critical concern in China given that the characteristics and influencing factors of residential PM 2.5 in China are not clear. What is added by this report?This study focuseed on residential PM 2.5 concentration of 12 cities with the on-site investigation in 2018, and provided th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The study did not exclude the factor of ventilation. Fan et al 24 reported the average concentration to be 79 μg/m 3 in 12 cities in 2018. It was a baseline investigation with limitations on the detecting environment.…”
Section: Introductionmentioning
confidence: 99%
“…The study did not exclude the factor of ventilation. Fan et al 24 reported the average concentration to be 79 μg/m 3 in 12 cities in 2018. It was a baseline investigation with limitations on the detecting environment.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic emission of PM2.5 can be analyzed by the concentration value after eliminating the influence of meteorological factors. The contamination baseline (CB) is characterized as the lowest limit of long-term anthropogenic impact on soil and atmospheric contamination [13][14][15]. The cumulative frequency curve method is the most commonly used approach for determining CB.…”
Section: Introductionmentioning
confidence: 99%